KECENDERUNGAN PENELITIAN PENDIDIKAN MATEMATIKA DI INDONESIA DENGAN FINLANDIA - Silangit, Menna Sri Ulina; Sembiring, Thresia Yohana; Purba, Ricky Rikardo; Sihombing, Dame Ifa; Manik, Efron (Universitas Quality, 2023)
The goals of this study are to (1) explain the trend of mathematics education research in Indonesia; (2) explain the trend of mathematics education research in Finland; and (3) compare research trends in mathematics education in Indonesia and Finland. The approach employed is a literature review, with the literature sources reviewed being journal articles, proceeding papers, books, and other publications linked to the trend of mathematics education research in Indonesia and Finland from 2019 to 2023 using the PoP (Publish or Perish) 8th edition. According to the findings of this study, the trend of educational research in Indonesia and Finland is dominated by educational research utilizing technology in mathematics learning.